Refleksi Asas Kemanfaatan: Mengilhami Asas Tiada Pidana Tanpa Kesalahan Tiada Kesalahan Tanpa Kemanfaatan - Nugroho, Fiska Maulidian; Eskanugraha, Andika Putra (Pusat Pengkajian Pancasila dan Konstitusi (PUSKAPSI) FH UNEJ, 2023)
The principle of no crime without fault is a fundamental principle, its existence does not seem to appear on the surface like the principle of legality contained in the criminal law law. However, the existence of this principle greatly influences the determination of the judge in imposing a sentence. By Indonesian criminal law officer, Romli Atmasasmita, he offers a complementary principle of the principle of no crime without error - no mistake without benefit. The references offered by Romli are very fundamental, both from a philosophical, sociological, and juridical perspective. Especially reviewing, the principle of expediency that exists side by side with two legal objectives, namely justice and legal certainty. The reflection on material criminal law offered by Romli through the reconstruction of this principle really inspires a point of view for anyone who studies the principle of guilt as the basis for criminal responsibility. It seems that it is time for legal education in Indonesia to look and reflect again, many criminal law officers in Indonesia are full of practical and theoretical experience (retired). The effect of the reconstruction of this principle should be interpreted as a legal view in the future, especially a strong legal structure by seeing and inspiring the Pancasila as the basis for balancing individual interests and the interests of society.